2019
DOI: 10.1016/j.trf.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the dependency of the drivers’ emotional experience on different road types and driving conditions

Abstract: The growing sophistication of technologies and sociological advances are major causes for the dramatic change the automotive sector is currently undergoing. To address changes from a human-centered design perspective an improved understanding of the occupants' emotional experience and behavior is required. Facial-Expression Analysis (FEA) is an emerging tool in support of such an approach, suitable for automotive research due to its noncontact application and low intrusiveness. The research described here inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
(77 reference statements)
1
3
0
Order By: Relevance
“…is is in line with Weber et al [50], and the possibility increases about 1.6% with the driver condition varying from the normal conditions to the unknown. Although most crashes happen under apparently normal conditions, the injury severity may be more severe under unknown conditions because the unknown makes the driving condition unpredictable.…”
Section: Resultssupporting
confidence: 92%
“…is is in line with Weber et al [50], and the possibility increases about 1.6% with the driver condition varying from the normal conditions to the unknown. Although most crashes happen under apparently normal conditions, the injury severity may be more severe under unknown conditions because the unknown makes the driving condition unpredictable.…”
Section: Resultssupporting
confidence: 92%
“…In real-world traffic, it is more reasonable that a driver would be angered or surprised by a pedestrian. As a matter of fact, it has been shown that anger and surprise are among the most frequently experienced negative emotions by drivers when driving on urban roads [114]. This comes as no surprise, as urban roads are characterized by high traffic density and a plethora of situations where the reckless or inconsiderate behaviour of another road user may pose a credible danger for the driver if evasive or corrective action is not undertaken immediately [98].…”
Section: Proposed Ehmi Conceptmentioning
confidence: 99%
“…On the contrary, in real-life traffic situations, it makes great sense that the reckless or inconsiderate behavior of a pedestrian would make a driver angry. In fact, previous research has shown that drivers experience anger very often when driving around the city [117]. This is to be expected, given the high traffic density that characterizes urban roads and the overabundance of situations where a driver may be delayed or even subjected to harm [99].…”
Section: Facial Expressions and Vehicle Non-yielding Intentionmentioning
confidence: 94%